2019
DOI: 10.1109/access.2019.2907159
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Modulation Recognition of Radar Signals Based on Manhattan Distance-Based Features

Abstract: Feature-based (FB) algorithms for automatic modulation recognition of radar signals have received much attention since they are usually simple to realize. However, existing FB approaches usually focus on several specific modulations and fail when applied to various modulations. To overcome this issue, we propose a simple and effective FB algorithm based on Manhattan distance-based features (MDBFs) in this paper. MDBFs are new features for radar signals that can be applied for recognition of different modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Therefore, if these two features are combined and expressed in one location, it is assumed to have a range for classifying fake keyboard data from the real keyboard data. To do this, the elapsed time and the scancode are expressed as X and Y coordinates, respectively, and the distance between the previous coordinate and the current coordinate is measured as the Manhattan distance, as shown in ( 3) [15]:…”
Section: ) Time-scancode Manhattan Distance Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if these two features are combined and expressed in one location, it is assumed to have a range for classifying fake keyboard data from the real keyboard data. To do this, the elapsed time and the scancode are expressed as X and Y coordinates, respectively, and the distance between the previous coordinate and the current coordinate is measured as the Manhattan distance, as shown in ( 3) [15]:…”
Section: ) Time-scancode Manhattan Distance Featurementioning
confidence: 99%
“…The other way is by measuring the elapsed time and scancode as X and Y coordinates, and calculating the Euclidean distance (i=2) from the previous coordinate to the current coordinate. Therefore, the distance between the previous coordinate and the current coordinate is expressed as Euclidean distance, as shown in ( 4) [15]:…”
Section: ) Time-scancode Euclidean Distance Featurementioning
confidence: 99%
“…Furui Wang et al (2019) proposed a vibration tone system method based on nonlinear ultrasonic characteristics, applied it to the monitoring of bolt joints, and found that the model could solve such problems as energy dissipation and low SNR ratio [ 15 ]. Yingkun Huang et al (2019) proposed a feature recognition algorithm for automatic modulation recognition of radar signals, applied it to the recognition of different modulation patterns, and found that the algorithm was almost unaffected by the signal pulse width, and would have high recognition effectiveness and robustness [ 16 ]. To solve the problems of modulation classification and symbol decoding, Ertan Kazikli and others (2019) proposed modulation recognition methods based on Bayesian framework and Minimax framework respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These signalling consist of information about the modulation and channel coding of different users and their allocated power. In order to suppress the overhead, we have proposed a novel receiver in which the modulation constellation of different users are identified by feature‐based automatic modulation classification (AMC) algorithms before symbol detection [17–36]; thereby the users do not need to be informed about their modulation schemes. We have proved a theorem which investigates the conditions under which a feature used for modulation classification (MC) in OMA scheme is also a feature for the case of two‐user NOMA (TU‐NOMA).…”
Section: Introductionmentioning
confidence: 99%